BETWEEN CRIME AND "DOXA": RESEARCHING THE WORLDS OF STATE-CORPORATE ELITES. (1st April 2012) - Whyte, David
Abstract : This article reflects upon some key theoretical and practical lessons of a research project on state-corporate elites in post-Saddam occupied Iraq. The research took place in a number of conferences organized to facilitate the neo-liberal transformation of the Iraqi economy following the 2003 invasion. The article begins with a brief summary of the theoretical and methodological approaches to the research which involved interviews with government officials and senior and middle managers in corporations that were exploiting the commercial opportunities opened up in the aftermath of the invasion and subsequent occupation. The article then revisits Cohen's ground-breaking work on state crime to explore how a research agenda - particularly a research agenda in the current era - might need to move beyond a theory of denial. Finally, the article proposes that Bourdieu's work on doxa and habitus provides researchers interested in state and corporate crime with a framework to approach and understand the worlds of the "powerful" and considers how this framework might usefully be applied.